2015
DOI: 10.1093/eurheartj/ehv455
|View full text |Cite
|
Sign up to set email alerts
|

Causes-of-death analysis of patients with cardiac resynchronization therapy: an analysis of the CeRtiTuDe cohort study

Abstract: AimsThe choice of resynchronization therapy between with (CRT-D) and without (CRT-P) a defibrillator remains a contentious issue. Cause-of-death analysis among CRT-P, compared with CRT-D, patients could help evaluate the extent to which CRT-P patients would have additionally benefited from a defibrillator in a daily clinical practice.Methods and resultsA total of 1705 consecutive patients implanted with a CRT (CRT-P: 535 and CRT-D: 1170) between 2008 and 2010 were enrolled in CeRtiTuDe, a multicentric prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 42 publications
9
69
1
1
Order By: Relevance
“…Patients receiving CRT-D had a mean age in their 60s in all studies, while the mean age of CRT-P patients was in their 70s in eight studies 3,14,27,30,33,37,38,50 . Overall, those receiving CRT-D were younger (65 years vs. 68.2) , more often males (80.3% vs. 72%), had lower NYHA class (60% in NYHA class 2 vs. 88.6%), lower prevalence of atrial fibrillation (21% vs.…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 95%
See 3 more Smart Citations
“…Patients receiving CRT-D had a mean age in their 60s in all studies, while the mean age of CRT-P patients was in their 70s in eight studies 3,14,27,30,33,37,38,50 . Overall, those receiving CRT-D were younger (65 years vs. 68.2) , more often males (80.3% vs. 72%), had lower NYHA class (60% in NYHA class 2 vs. 88.6%), lower prevalence of atrial fibrillation (21% vs.…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 95%
“…Two-hundred and thirtyseven were retrieved for analysis of titles and abstracts and 49 of these were selected for further analysis of the full-length article. Eighteen were considered eligible for inclusion 3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Search Results and Patients' Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…While some argue that any patient treated with CRT should also receive defibrillator backup,7 others counsel restraint in adding additional device functions 8, 9. A recent cohort study adjudicated cause of death for patients with CRT‐P versus CRT‐D and found that the vast majority of excess mortality in CRT‐P patients was non‐sudden death, weakening the argument for default defibrillator backup 10. Preventing sudden cardiac death with an implantable cardioverter‐defibrillator (ICD) is distinct from improving heart failure symptoms, and not every patient views these as necessarily linked 11.…”
mentioning
confidence: 99%